2017
DOI: 10.7150/thno.17665
|View full text |Cite
|
Sign up to set email alerts
|

Suppression Of β-catenin Nuclear Translocation By CGP57380 Decelerates Poor Progression And Potentiates Radiation-Induced Apoptosis in Nasopharyngeal Carcinoma

Abstract: Nuclear localization of β-catenin is essential for the progression of various human cancers via transcriptional upregulation of downstream genes. The MAP kinase interacting serine/threonine kinase (MNK)-eukaryotic translation initiation factor 4E (eIF4E) axis has been reported to activate Wnt/β-catenin signaling, and CGP57380, an inhibitor of MNK kinases, inhibits the proliferation of multiple cancers. In this study, we showed that β-catenin signaling (including β-catenin, cyclin D1, c-Myc, and MMP-7) and p-eI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 53 publications
(57 reference statements)
3
43
0
Order By: Relevance
“…Cell wound healing was performed as previously described . Cell migration was assessed by transwell assays.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell wound healing was performed as previously described . Cell migration was assessed by transwell assays.…”
Section: Methodsmentioning
confidence: 99%
“…Cell wound healing was performed as previously described. 10 Cell migration was assessed by transwell assays. Briefly, 1 × 10 5 cells in serum-free RPMI-1640 were seeded on a membrane (8.0-μm pore size) inserted in the wells of a 24-well plate.…”
Section: Cell Wound Healing Migration and Invasion Assaysmentioning
confidence: 99%
“…Our previous study has demonstrated that β-catenin pathway was abnormally activated in NPC (including β-catenin, cyclin D1, c-Myc and MMP7), we found that these proteins were abnormally activated in NPC compared with non-cancerous nasopharyngeal mucosa, and patients with aberrant β-catenin expression and overexpression of cyclin D1, c-Myc and MMP7 might have worse survival outcome 3. Normally, due to lack of β-catenin in nucleus, lymphoid enhancer factor (LEF)/transcription factor (TCF) combine with other proteins and repress target genes, and thus inhibit cell proliferation.…”
Section: Introductionmentioning
confidence: 71%
“…Based on our previous study, β-catenin pathway was abnormally activated in NPC (including β-catenin, cyclin D1, c-Myc and MMP7), and patients with aberrant β-catenin expression and overexpression of cyclin D1, c-Myc and MMP7 might have worse survival outcome 3. As the important components of the canonical Wnt/β-catenin pathway, LEF/TCF are confirmed to be abnormal in many malignant tumours.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have reported that the Wnt/β-catenin pathway is related to cell development and proliferation [23][24][25]. Therefore, the present study considered the Wnt/β-catenin pathway as a target pathway for aspirin-induced apoptosis.…”
Section: Aspirin Inhibited the Canonical Wnt/β-catenin Pathway Of Tscmentioning
confidence: 97%